STUDI STATUS HARA N, P DAN K UNTUK TANAMAN PADI PADA LAHAN PASANG SURUT DI DESA SARANG BURUNG KOLAM KECAMATAN JAWAI KABUPATEN SAMBAS - Susi Sartika, Susi sartika (Fakultas Pertanian Universitas Tanjungpura, 2016)
ABSTRACT This study aimed to determine the status of nutrients N, P and K at research site for the development of rice and fertilizer recommendation for tidal wetland in the study site. The research was conducted in Agustus - December 2015 in Sarang Burung Kolam village precisely in the hamlet Buluh Perindu Jawai Subdistrict Sambas Regency with a land area of 3,5 ha. The method used in this research was survey. Variables of observation in this research include pH, N-total, P-available, K-dd, DHL, pyrte test and calculation of fertilizer requirements. The result of analysis shows that pH is relatively netral